Profitability versus cash flow: which is a better determinant of dividends per share - Teo, Levi (2018)
The objective of this study was to determine which determinant is the better determinant for dividends in the KLCI, Profitability or Cash flow? This study identified the two schools of thought that attempts to explain how dividends are determined: Profitability is a Signalling Theory Proponent, and Liquidity is an Agency Cost Theory Proponent. This report explores from the literature on theories can be used for this study, mainly the Modigliani and Miller theory of Irrelevance of Dividends, and other school of thoughts. Data of the 30 Firms in the KLCI were collected, with data ranging from fiscal year 2006 until fiscal year 2015. The data is analysed using Panel Analysis with Pooled Regression, Fixed Effect, and Random Effects. A robustness test was conducted by removing Bank from the sample and analysed using Panel Analysis. The main finding in the results is Profitability (ROA) is significant and positive determinant of Dividends, whilst Liquidity or Cash Flow (both Free Cash Flow and Operating Cash Flow) is not significant. This shows that Signalling theory is a reliable theory to determine Dividends in the KLCI whilst Agency Cost is not reliable theory to determine Dividends in the KLCI. The result answers the objective of this study, that Profitability is the best determinant of dividends of large capitalization firms in the KLCI. An additional finding was discovered in the analysis: Expensiveness of stocks or Market-To-Book Ratio (MBR) is a reliable and significant positive determinant of dividends in the KLCI. The robustness test produced similar results: profitability is a positive determinant and cash flow is not determinant.